Metal oxide surge arrester design for ultra high voltage transmission lines - Trabulus, S (IEEE, 2000)
Each year as Cine and system loadings increase due to the energy request and mon operating companies superimpose higher voltage transmission systems on existing facilities, the ultra high cottage power systems come mon to the fore Since Be metal oxide surge arresters have an important role in the insulation coordination of all power system in this papa the present development state and Le different design criteria of the metal oxide surge arresters are especially taken for Be ultra high voltage transmission lines of 1000 kV into account.
Keywords: TIME; Computer Science; Energy & Fuels; Engineering